2020
DOI: 10.47895/amp.v54i1.1111
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochemical Content and the In vitro Antifungal Properties of Senna alata (Linn.) Roxb.: A Review

Abstract: Infections caused by invasive fungal species continue to rise due to various contributing factors including the changes in the environmental and weather conditions, lifestyle, the occurrence of natural disasters, and the weakened human immune system. Even though synthetic drugs effectively cure fungal diseases, their unwanted side effects, as well as the rapid rise in resistance, have compelled researchers to develop new antifungal agents. Several medicinal plants are folklorically known to have antifungal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
(26 reference statements)
0
10
0
1
Order By: Relevance
“…Senna alata has been used for a long time for the treatment of tinea versicolor and ringworm infections in Thailand [2]. In the Philippines, clinical trials have also confirmed the usefulness of S. alata as a topical agent in treating fungal skin infections [3]. In Cameroon, S. alata is used for the treatment of several infections including: gonorrhea, gastro-intestinal and skin diseases [15].…”
Section: Anti-microbialmentioning
confidence: 99%
See 3 more Smart Citations
“…Senna alata has been used for a long time for the treatment of tinea versicolor and ringworm infections in Thailand [2]. In the Philippines, clinical trials have also confirmed the usefulness of S. alata as a topical agent in treating fungal skin infections [3]. In Cameroon, S. alata is used for the treatment of several infections including: gonorrhea, gastro-intestinal and skin diseases [15].…”
Section: Anti-microbialmentioning
confidence: 99%
“…The antimicrobial bioactivity is related to its secondary metabolites. The compound anthraquinones [3], tannins, steroids, alkaloids, anthraquinones, terpenes and saponins [20,24] is the main compound responsible for the antifungal activity [3]. Anthraquinone aglycans are compounds that inhibit the growth of C. albicans [2].…”
Section: Anti-microbialmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent review 27 , the plant's ethanolic, aqueous, methanolic and hexane leaf, stem and root extracts have activities against Aspergillus flavus, A. niger, A. parasiticius, Candida albicans, C. neoformans, Epidermophyton floccosum, M. canslaslomyces, M. canis, M. gypseum, M. audouinnii, T. verrucosim, T. megnini, T. mentagrophytes, T. rubrum, T. tonsurans, and Penicillium marneffei. In addition, its ethanolic extract showed excellent activity and is favorable in formulating a topical treatment for those infected with these fungi.…”
Section: Introductionmentioning
confidence: 99%